Human DNA damage by the synergistic action of 4‐aminobiphenyl and nitric oxide: An immunochemical study. Issue 5 (19th May 2012) - Moinuddin,; Dixit, Kiran; Ahmad, Saheem; Shahab, Uzma; Habib, Safia; Naim, Mohammad; Alam, Khursheed; Ali, Asif
<x xml:space="preserve">Abstract</x> 4‐Aminobiphenyl (4‐ABP), an aromatic amine is a major environmental carcinogen found mainly in cigarette smoke. It has been vastly implicated in mutagenesis and cancer development. In this study, commercially available human placental DNA was exposed to 4‐ABP (1.3 mM) in presence of sodium nitroprusside (SNP; 8 mM) at 37°C for 3 h. The 4‐ABP + SNP‐mediated structural changes in human DNA were studied by ultraviolet, circular dichroism and fluorescence spectroscopy, thermal melting profile, agarose gel electrophoresis, and nuclease S1 digestibility assay. Spectroscopical analysis and melting temperature studies suggest structural perturbations in the DNA as a result of modification. This might be due to generation of single‐stranded regions and destabilization of hydrogen bonds. Modification was also visualized in agarose gel electrophoresis. Furthermore, nuclease S1 digestibility confirmed the generation of single strand breaks. Rabbits challenged with 4‐ABP‐SNP‐modified human DNA‐induced high‐titer immunogen‐specific antibodies, which showed Cross‐reaction with modified/unmodified DNA bases and ss‐DNA in competitive inhibition assay. The immunogen specificity of induced antibodies against 4‐ABP‐SNP‐modified human DNA was further confirmed in gel retardation assay. It may be concluded that induction of anti‐modified DNA antibodies could be due to perturbation in the DNA structure and its subsequent recognition by immunoregulatory cells as a foreign molecule. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 568–576, 2014.